Biochemical properties of a Flavobacterium johnsoniae dextranase and its biotechnological potential for Streptococcus mutans biofilm degradation - Pozelli Macedo, Maria Júlia; Xavier-Queiroz, Mateus; Dabul, Andrei Nicoli Gebieluca [UNESP]; Ricomini-Filho, Antonio Pedro; Hamann, Pedro Ricardo Viera; Polikarpov, Igor (Springer Nature, 2024)
Cariogenic biofilms have a matrix rich in exopolysaccharides (EPS), mutans and dextrans, that contribute to caries development. Although several physical and chemical treatments can be employed to remove oral biofilms, those are only partly efficient and use of biofilm-degrading enzymes represents an exciting opportunity to improve the performance of oral hygiene products. In the present study, a member of a glycosyl hydrolase family 66 from Flavobacterium johnsoniae (FjGH66) was heterologously expressed and biochemically characterized. The recombinant FjGH66 showed a hydrolytic activity against an early EPS-containing S. mutans biofilm, and, when associated with a α-(1,3)-glucosyl hydrolase (mutanase) from GH87 family, displayed outstanding performance, removing more than 80% of the plate-adhered biofilm. The mixture containing FjGH66 and Prevotella melaninogenica GH87 α-1,3-mutanase was added to a commercial mouthwash liquid to synergistically remove the biofilm. Dental floss and polyethylene disks coated with biofilm-degrading enzymes also degraded plate-adhered biofilm with a high efficiency. The results presented in this study might be valuable for future development of novel oral hygiene products.
Keywords: Dextranase; GH66; Oral biofilms; Streptococcus mutans; Synergy